$\large \log_{b}{(m)} = \dfrac{1}{\log_{m}{(b)}}$

The quantity and base in a logarithmic term can be switched by changing the base in reciprocal form. It is called as base switch rule of logarithms and it is used as a formula in logarithmic mathematics.

The change of base formula for logarithm in reciprocal form is derived in logarithmic mathematics by using the rules of exponents and mathematical relation between exponents and logarithms.

$\log_{b}{m}$ and $\log_{d}{b}$ are two logarithmic terms and it is assumed that the values of them are $x$ and $y$ respectively.

$\log_{b}{m} = x$ and $\log_{d}{b} = y$

The equations in logarithmic form can be written in exponential form by the mathematical relationship between exponents and logarithms.

$(1) \,\,\,$ $\log_{b}{m} = x \,\Leftrightarrow\, m = b^{\displaystyle x}$

$(2) \,\,\,$ $\log_{d}{b} \,\,\, = y \,\Leftrightarrow\, b = d^{\displaystyle y}$

The change of base formula can be written in mathematical form by this data.

$\log_{b}{m} = \dfrac{\log_{d}{m}}{\log_{d}{b}}$

Take $d = m$ and eliminate $d$ by $m$ in the change of base formula.

$\implies$ $\log_{b}{m} = \dfrac{\log_{m}{m}}{\log_{m}{b}}$

Mathematically, the logarithm of a quantity (equals to base) is always one as per log base rule. Therefore, $\log_{m}{m} = 1$ and write the change of base formula.

$\,\,\, \therefore \,\,\,\,\,\,$ $\log_{b}{m} = \dfrac{1}{\log_{m}{b}}$

Latest Math Topics

Jul 20, 2023

Jun 26, 2023

Jun 23, 2023

Latest Math Problems

Jul 01, 2023

Jun 25, 2023

Copyright © 2012 - 2023 Math Doubts, All Rights Reserved